Cruel, Inhuman or Degrading Treatment? Benefit Sanctions in the UK - Adler, Michael (Palgrave Socio-Legal Studies, 2018)
The book subjects the largely hidden phenomenon of benefit sanctions in the UK to sustained examination and critique. It comprises twelve chapters dealing with the terms 'cruel', 'inhuman' and 'degrading' that are used as a benchmark for assessing benefit sanctions; benefit sanctions as a matter of public concern; the historical development of benefit sanctions in the UK; changes in the scope and severity of benefit sanctions; conditionality and the changing relationship between the citizen and the state; the impact and effectiveness of benefit sanctions; benefit sanctions and administrative justice; the role of law in protecting the right to a social minimum; a comparison of benefit sanctions with court fines; benefit sanctions and the rule of law; and what, if anything, can be done about benefit sanctions. Each chapter ends with a paragraph that attempts to highlight the most salient points in that chapter, and the book ends with a short conclusion in which benefit sanctions are assessed against the chosen benchmark.